Digital disobedience and the law. Issue 3 (2nd July 2016) - Scheuerman, William E.
Abstract: Digital disobedience can be defined as politically motivated online lawbreaking. It includes Distributed Denial of Service actions, hacktivism, digitally based leaking (for example, Anonymous, Wikileaks), and whistleblowing (along the lines pursued by Chelsea Manning and Edward Snowden). Given its growing political importance, the phenomenon requires careful theoretical attention. Against the widespread tendency to criminalize digital disobedience by appealing to conventional notions of the 'rule of law', this article argues that some of its proponents are in fact engaging in digital lawbreaking as expressions of their fundamental respect for the rule of law. Although this diagnosis highlights the partial overlap with conventional models of civil disobedience (which oftentimes similarly conceive of politically motivated lawbreaking as necessarily resting on a more fundamental respect for the law), we should hesitate before viewing digital disobedience simply as modernized or digitalized civil disobedience. Digital disobedience includes some political novelties, and traditional views of civil disobedience only get us so far in making sense of those novelties.